Using Dictyostelium to Advance Our Understanding of the Role of Medium Chain Fatty Acids in Health and Disease - Pain, Erwann; Shinhmar, Sonia; Williams, Robin S. B. (Frontiers in Cell and Developmental Biology, 2021)
Ketogenic diets have been utilized for many years to improve health, and as a dietary approach for the treatment of a range of diseases, where the mechanism of these low carbohydrate and high fat diets is widely considered to be through the production of metabolic products of fat breakdown, called ketones. One of these diets, the medium chain triglyceride ketogenic diet, involves high fat dietary intake in the form of medium chain fatty acids (MCFAs), decanoic and octanoic acid, and is commonly used in endurance and high intensity exercises but has also demonstrated beneficial effects in the treatment of numerous pathologies including drug resistant epilepsy, cancer and diabetes. Recent advances, using Dictyostelium discoideum as a model, have controversially proposed several direct molecular mechanisms for decanoic acid in this diet, independent of ketone generation. Studies in this model have identified that decanoic acid reduces phosphoinositide turnover, diacylglycerol kinase (DGK) activity, and also inhibits the mechanistic target of rapamycin complex 1 (mTORC1). These discoveries could potentially impact the treatment of a range of disorders including epilepsy, cancer and bipolar disorder. In this review, we summarize the newly proposed mechanisms for decanoic acid, identified using D. discoideum, and highlight potential roles in health and disease treatment.